Dom IRIS in njegova vloga v rehabilitaciji - Ocepek, Julija (Rehabilitacija (Ljubljana), 2010)
Smart Home IRIS is a demonstrative apartment, founded in 2008 on the basis of numerous European smart home projects. The aim of this study was to establish the role of Smart Home IRIS in improving quality of life for persons with disabilities and elderly in Slovenia and the satisfaction of persons who have already been involved in a treatment in it. We analyzed a satisfaction questionnaire of the treatment in Smart Home IRIS, sent to all patients in 2008 (79 in total), as well as the problems, identified by patients in the Canadian Occupational Performance Measure (COPM). We received 36 correctly filled-in questionnaires; 11 respondents were women and 25 men, with a mean age of 44.2 years (range 18-80 years) and with different diagnoses. The analysis of the satisfaction questionnaire showed that the patients received several services. The information and solutions suggested by professionals were partially implemented; information and solutions have a medium influence on the quality of their life. In the COPM, patients identified the problems that lead to treatment in the Smart Home IRIS. The patients were satisfied with the treatment and the professionals' work in the Smart Home IRIS. Establishment of Smart Home IRIS significantly contributes to a better quality of life, which is the main aim of rehabilitation.
Keywords: bivanje; Dom IRIS; invalidi; kakovost življenja; pametne stavbe; rehabilitacija; standard of living; starostniki; vocational rehabilitation